Formality shifts in management meetings - Mohd Johari, Muhammad Danis (2016)
Studies on Business English (BE) are becoming a growing interest with the trend in past studies moving from the importance of BE to improving it. The main objective of this study is to analyze formality shifts in management meetings. It’s specific objectives include the analysis of linguistic devices, language strategies, and the effects of power-play in order to see how all of these contribute to formality shifts in the meetings. Heylighen and Dewaele (1999) provided a theoretical framework to analyze the overall formality of a setting but lacked sufficient explanation on the factors of formality. This study adapted their framework and also from past studies on formality such as by Rogerson-Revell (2007). Conversational Analysis (CA) was used to analyze the transcribed data. Findings revealed that informality is caused by an increased in shared context which creates shorter and more casual turn takings as seen through the use of small talk and humour caused digression during a meeting. Furthermore, discourse markers were used to shift the meeting to being formal. Interestingly, the shift from formal to informal in a meeting was dependent on the manager’s participation. Meetings had more formality when the manager was present as lower ranked participants were less informal in the attempt to manage rapport. In conclusion, the participants’ position in the company determines the manner of speech being used in a meeting which results in the linguistic devices that cause change in a meeting’s formality.